2014
DOI: 10.1074/jbc.m114.551143
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Cancer-associated Mutations Disable Catalytic Activity of CDK12, a Kinase That Promotes Homologous Recombination Repair and Resistance to Cisplatin and Poly(ADP-ribose) Polymerase Inhibitors

Abstract: Background: CDK12 mutations occur in ovarian cancer. Results: These mutations impaired CDK12 kinase activity. Additionally, disabling CDK12 in ovarian cancer cells reduced BRCA1 levels and disrupted homologous recombination repair. Conclusion: CDK12 mutations that impair kinase activity likely disrupt homologous recombination. Significance: Defects in homologous recombination caused by CDK12 mutations may predict sensitivity to chemotherapy agents, including poly(ADP-ribose) polymerase inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
179
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(194 citation statements)
references
References 33 publications
4
179
1
5
Order By: Relevance
“…The DDR and the AR pathways have both been linked with mechanisms of cisplatin resistance in ovarian cancer cells [41,42,44,58,59]. It is conceivable that these two pathways work concertedly to reduce the susceptibility of ovarian cancer cells to cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…The DDR and the AR pathways have both been linked with mechanisms of cisplatin resistance in ovarian cancer cells [41,42,44,58,59]. It is conceivable that these two pathways work concertedly to reduce the susceptibility of ovarian cancer cells to cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…Effect of CDK12 knockdown in cellular models has been consistently associated with HRD (3,5,7,8). HRD in breast and ovarian cancers is mostly related to BRCA1/2 inactivation (9-11).…”
Section: Cdk12 Td-plus Phenotype and Genomic Hrd Hallmarksmentioning
confidence: 99%
“…CDK12 encodes a serine/threonine kinase involved in the regulation of RNA polymerase II (RNA pol II) and mRNA processing (2)(3)(4). CDK12 attracted particular attention as cells inactivated for the CDK12 display hypersensitivity to DNA-damaging agents and to PARP1/2 inhibitors (5,6). This effect of CDK12 inactivation was associated with homologous recombination (HR) deficiency (HRD) due to decreased expression observed for some HR genes, such as BRCA1, FANCI, or FANCD2 (3,5,7,8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Additionally, we have recently demonstrated that dinaciclib is the most potent inhibitor of CDK12 known thus far, and therefore a transcriptional regulator of HR genes. [7][8][9][10] We comprehensively examined the combination of dinaciclib and PARP inhibitors, such as veliparib and olaparib, in preclinical models of triple-negative breast cancer (TNBC), including BRCA wild-type cells, BRCA-mutated cells, and patient-derived xenograft (PDX) models of primary and acquired resistance to PARP inhibition. 10 First, pathway analyses demonstrated that the genes downregulated by dinaciclib in BRCA wild-type TNBC cells were significantly enriched for those involved in HR repair and DNA damage-sensing, including BRCA1 and RAD51.…”
mentioning
confidence: 99%